INTERNATIONALIZATION AND ACADEMIC PARTNERSHIPS BETWEEN UNIVERSITIES - Roshka, Petru; Trifonova, Larisa (Sworld-Us Conference proceedings, 2023)
This research article explores the role of internationalization and academic partnerships in the context of contemporary higher education. Internationalization, as a strategic tool, has a significant impact on the development of universities, as well as t